ANAYLISIS OF UNDERPRICING FACTORS ON INITIAL PUBLIC OFFERING (IPO) ON IN THE INDONESIA STOCK EXCHANGE - Willy Cahya Sundara; Adler Haymans Manurung; I Gusti Ketut Agung Ulupui; Agung Dharmawan Buchdadi (International Journal Labs, 2022)
Initial Public Offering (IPO) is known as one of the efforts to obtain a source of funds for a company in order to develop the business to be optimal. Capital is the funds used for investment by the owner in running his business. A company or business definitely requires additional funds, so that the company's operations can run optimally and develop more. When an IPO experiences a difference in stock prices, there are terms underpricing and overpricing. The purpose of this study was to determine the factors that influence underpricing at the time of the IPO on the Indonesian stock exchange. The method used in this study is a descriptive method with a qualitative approach. The results of thr study show that the underpricing factors on Initial Public Offering (IPO) On In Indonesia Stock Exchange are profitability, leverage, underwriter reputation, company size, and percentage of stock offered against underpricing.